Kewenangan Hakim Dalam Menjatuhkan Putusan Perkara Pembunuhan Sesuai Undang-Undang Kekuasaan Kehakiman - Shyandra Putri Buhang; Fence M Wantu; Nuvazria Achir (Lembaga Pengembangan Kinerja Dosen, 2024)
the study aims to analyze the imposition of a criminal verdict in the case of murder that occurred in case No. 117/PID.B / 2022 / PN GTO at the Gorontalo City District Court, as well as factors that influence the judge in deciding the murder case. The research method used is normative legal research with the approach of legislation and the approach of existing cases, which are then analyzed in a descriptive qualitative. The results showed that the analysis of the verdict on the murder case No. 117/Pid.B / 2022 / PN GTO at the Gorontalo City District Court, it can be concluded that the decision is the result of a criminal justice process based on the results of the examination and the facts of the trial as well as the cooperative attitude of the perpetrator. The factors that influence the decision, among others, are the evidence presented in the trial, witness testimony, Judge's consideration, and applicable legal provisions. The judge in his decision did not consider the elements of the indictment charged by the public prosecutor, namely Article 340 of the criminal code, but instead decided the case using Article 338 of the Criminal Code which, according to researchers, does not reflect the principle of legal certainty and Justice.